CASE REPORT: UNCONTROLLED HYPERTENSION CONTRIBUTES TO WORSENING OF PRESBYCUS SYMPTOMS IN THE ELDERLY - Saputri, Faradila Budi; Firdha, Azizah Amimathul; Rahma, Safira; Alda, Rieza Rizqy; Inayasari, Syahwina; Purnami, Nyilo (Journal of Community Medicine and Public Health Research, 2020)
Presbycusis is a disease that can befall the elderly, caused by a multifactorial process that should be allowed to disrupt communication and social life and cause mental disorders. According to WHO the proportion of the elderly population rises rapidly which is estimated in 2025, there are about 1,2 billion elderly people with a risk of presbycusis. Mr.S was 84 years old, married and had 2 children, complained of hearing loss since 10 years ago on the patient's left ear. The decline in hearing occurred gradually, giving the last 4 years after his wife's death. Patients was taken to Otorhinolaryngologist and expressed age-related hearing impairment and was advised to use hearing aids. Patients are not routinely using hearing aids. In addition, patients have hypertension and heart disease. Patients consumed Captopril 2x1 tablets, Fundifar 2x1, Furosemide 1x40 mg and Fargoxin 1x0.25 mg. Patients do not routinely consumed cardiac medicine and used hearing aids. From the results of heteroanamnesis, physical examination, and audiogram examination conducted in Mr.S patients, it can be concluded that Mr.S suffers from presbycusis with hypertensive and congestive heart failure. Mr.S was advised to routinely have their hearing check to Otorhinolaryngologist the as an evaluation and routine control to Cardiologist.